ROLE OF ART IN BUSINESS: INTEGRATING VISUAL AND PERFORMING ARTS TO FOSTER CREATIVITY, DRIVE INNOVATION, AND ENHANCING STRATEGIC OUTCOMES - Saha, Animesh; Mukherjee, Subhendu; Sharma, Dhanesh (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper explores the integration of visual and performing arts into business practices as a strategic tool to foster creativity, drive innovation, and enhance organizational outcomes. By synthesizing literature and case studies, it highlights how arts-based methods, such as design thinking and improvisation, stimulate imaginative problem-solving, collaboration, and emotional intelligence. Visual arts enable the visualization of abstract concepts and diverse perspectives, while performing arts strengthen adaptability, communication, and team dynamics. These approaches break traditional silos, promote experimentation, and cultivate inclusive cultures of innovation. The paper provides a theoretical framework and practical recommendations for integrating arts into business strategies, demonstrating how organizations can achieve a competitive edge through creativity-driven innovation. Findings emphasize the measurable impacts of arts-based practices on employee engagement, team cohesion, and organizational culture, addressing gaps in existing research. The study underscores the value of interdisciplinary collaboration, inspiring businesses to leverage artistic approaches for sustainable growth in today’s complex, dynamic environments.